Complex Insect–Pathogen Interactions in Tree Pandemics - Santini, Alberto; Battisti, Andrea (Frontiers in Physiology, 2019)
Tree pandemics are a major cause of economic and ecological loss in forest and urban ecosystems. They often depend on the introduction of a non-native pathogen, which is occupying the niche of a native, nonaggressive organism. Complex interactions with native insects carrying fungi and nematodes can be established based on the proximity of the aggressive pathogenic agents. Here we review three major pandemics of forest and urban trees in temperate ecosystems at world scale, i.e. the Dutch elm disease, the cypress canker, and the pine wilt disease. For each system, the relationships between aggressive and nonaggressive fungi and nematodes with the native insect vectors are presented. Hidden players such as insects, microorganisms or plants, which may have the role of facilitating or contrasting the performance of the agents, are also considered. Results suggest that pandemics rely on the introduction of a non-native pathogen that exploits well-developed interactions between native nonaggressive organisms and insects associated with trees. The success of the invaders depends on the morpho-physiological proximity of the players and on the mutual benefits resulting from the associations. Deciphering such interactions in native systems may help to predict the outcome of the introduction of new pathogens and the development of new tree pandemics.